Autologous Resurfacing and Fracture Dowelling A Manual of Transplantation Technique - Draenert, Klaus; Draenert, Yvette; Pohlemann, Tim.; Regel, Gerd.; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2012)
This book describes in detail a unique and very precise operative technique that uses autologous cartilage/bone grafts for the reconstruction of load-bearing joint surfaces and for dowelling of non-unions. The technique, employing diamond instruments and a wet grinding process, has been developed and refined over the past 30 years at the Center for Orthopaedic Sciences (ZOW), first in Bern and later in Munich. A step-by-step description of the method is provided for each indication, with the aid of many high-quality illustrations. Correctly applied, the technique has been very successful in restoring high-level athletes to competition; it can be applied even in hopeless cases and offers excellent late results. This guide will be invaluable for orthopaedic surgeons wishing to master this proven and effective approach.
Historical Background -- Microscopical Anatomy -- Growth -- Turnover and Healing Processes -- Bone Substitutes -- Cartilage-Bone Grafting -- Clinical Practice of Autologous Resurfacing® -- Fracture Dowelling -- Instrumentation.
Keywords: Medicine; Orthopedic surgery; Medicine & Public Health; Surgical Orthopedics